2023
DOI: 10.1093/pubmed/fdad144
|View full text |Cite
|
Sign up to set email alerts
|

Association between individual resilience and depression or anxiety among general adult population during COVID-19: a systematic review

Abstract: Background The coronavirus disease (COVID-19) pandemic exacerbated depression and anxiety worldwide. Resilience is important to maintain mental health during uncertain times, but limited study has systematically reviewed its association with depression or anxiety with an emphasis on the general population. Methods We searched PubMed and Embase for quantitative or mixed-methods studies on the general adult population published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Variables such as sex, COVID-19 exposure, fear, and isolation were also associated with resilience. Similarly, in a 2023 systematic review of 35 studies that assessed resilience and anxiety/depression simultaneously, 8 studies demonstrated no significant associations linking resilience to anxiety and depression ( 50 , 51 ). We acknowledge that the significant statistical associations reported in our study raise hypotheses but do not constitute evidence of causal links between resilience and mental-health symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Variables such as sex, COVID-19 exposure, fear, and isolation were also associated with resilience. Similarly, in a 2023 systematic review of 35 studies that assessed resilience and anxiety/depression simultaneously, 8 studies demonstrated no significant associations linking resilience to anxiety and depression ( 50 , 51 ). We acknowledge that the significant statistical associations reported in our study raise hypotheses but do not constitute evidence of causal links between resilience and mental-health symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Based on self-reported data from 2021 SAMHSA reports, women had a higher prevalence of major depressive episodes (10.3%) than men (6.2%), and young adults aged 18 to 25 had the highest prevalence (18.6%) [ 59 ]. Resilience has been shown to be protective against daily and chronic stressors and to reduce the risk of depression—a risk factor for poor diet quality and related CVD outcomes [ 14 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Our findings and those of others suggest that resilience is significantly and positively associated with diet quality, even after adjusting for socioeconomic status and depression [ 46 , 70 ].…”
Section: Discussionmentioning
confidence: 99%